Biological and Residual Activity of Candidate Larvicide Formulation, SumiLarv TM 2MR, against an Exotic Invasive Mosquito Anopheles stephensi Liston in Ethiopia - Yehwalaw, Delenasaw; Erena, Ebisa; Degefa, Teshome; Zemene, Endalew; Simma, Eba A.; Kifle, Yehenew Getachew (My University, 2025)
The study assessed the efficacy and residual activity of SumiLarvᵗᵐ 2MR, SumiLarvᵗᵐ 0.5G, and Abate® 1SG (as a positive control) against Anopheles stephensi larvae in Awash Subath Kilo, Afar Regional State, Ethiopia. A semi-field experiment used plastic containers with capacities of 100L, 250L, and 500L. For SumiLarvᵗᵐ 2MR, four 100L containers were treated with one disc each, compared to two untreated controls. Similarly, four 250L containers were treated with one disc each with two untreated controls. Eight 250L containers were treated with a half-dose to match one disc per 500L, alongside four untreated controls. For SumiLarvᵗᵐ 0.5G and Abate 1SG, four 100L containers were treated with each larvicide, with two untreated controls. Each container received 2025 third and fourth instar An. stephensi larvae. Observations of adult emergence were conducted until all pupae either emerged or died. The result revealed that SumiLarvᵗᵐ 2MR had a nine-month residual efficacy, SumiLarvᵗᵐ 0.5G had a seven-week efficacy, and Abate 1SG had a five-week efficacy. SumiLarvᵗᵐ 2MR discs retained nearly 50% of their initial pyriproxyfen content after nine months, indicating potential for extended residual activity. The study highlights SumiLarvᵗᵐ 2MR's long-term efficacy as a larvicide against An. stephensi in Ethiopia.